Indicators of productivity of pigs for different contents of the enzyme prepara-tion “Celozym” - O. V. Voitsitskyi; N. V. Novgorodska (Науковий вісник Львівського національного університету ветеринарної медицини та біотехнологій імені С.З. Гжицького. Серія: Сільськогосподарські науки)
Breeding animals in modern industrial conditions with intensive technologies places a high demand on keeping animals. Combining the biological features of the animal organism with the technological process makes it possible to obtain high productivity while reducing the cost of livestock products obtained from them. Feeding is important in animal husbandry, only with optimal feeding, animals will have good health and be highly productive with minimal costs for the products obtained. In this regard, it is necessary to improve the technology of feed preparation and the use of various feed additives. Currently, enzyme preparations are widely used as a feed additive in animal feeding both in Ukraine and abroad. Enzyme preparations are added either to complete feed or to the composition of the diet. We experimented with introducing the enzyme preparation “Celozym” into the pigs' diet. This drug was administered at several stages of growing animals, for this purpose a comparative period was conducted, and all indicators were compared relative to the control group, which remained without the effect of this drug. The experiment was conducted at the agricultural enterprise “Ukraine” of Vinnytsia district, Vinnytsia region. It was established that using the enzyme preparation “Tselozym” as part of compound feed increased the productivity of the young pigs of the experimental groups compared to the control counterparts. Still, the highest indicators were obtained when 0.6 kg/t of the enzyme preparation was added to the compound feed. The introduction of the enzyme drug “Celozym” into the diet of fattening pigs increases the intensity of growth and fattening of young pigs, reduces feed costs per unit of production.